Viral DNAemia and Immune Suppression in Pediatric Sepsis. Issue 1 (January 2018) - Davila, Sam; Halstead, E. Scott; Hall, Mark W.; Doctor, Allan; Telford, Russell; Holubkov, Richard; Carcillo, Joseph A.; Storch, Gregory A.
Abstract : Objectives: Demonstrate that DNA viremia is common in pediatric sepsis and quantitate its associations with host immune function and secondary infection risk. Design: Retrospective analysis of a prospective cohort study. Patients: Seventy-three children admitted with sepsis-induced organ failure. Interventions: None. Measurements and Main results: This study was performed as an ancillary investigation to a single-center prospective study of children with severe sepsis. Longitudinally collected, batched, frozen plasma was examined using real time–polymerase chain reaction for the presence of cytomegalovirus, Epstein-Barr virus, herpes simplex virus, human herpes virus-6, torque teno virus, and adenovirus DNA. Innate immune function was also measured longitudinally via quantification of ex vivo lipopolysaccharide -induced tumor necrosis factor-α production capacity. Viral DNAemia with a virus other than torque teno virus was detected in 28 of 73 subjects (38%) and included cytomegalovirus 5%, Epstein-Barr virus 11%, herpes simplex virus 4%, human herpes virus-6 8%, and adenovirus 26%. In addition, torque teno virus was detected in 89%. Epstein-Barr virus DNAemia was associated with preexisting immune suppression ( p = 0.007) Viral DNAemia was associated with preexisting immune suppression and high risk for the subsequent development of secondary infection ( p < 0.05 for both). Subjects with viral DNAemia had lower innate immune function over time compared with those who were virus negative ( p < 0.05). Conclusions: DNAemia from multiple viruses can be detected in septic children and is strongly associated with preexisting immune suppression and secondary infection risk. The role of DNA viruses in the perpetuation of impaired host defense in this setting should be the subject of prospective study.